Tax Barden on the Enterprise in Ukraine - Sytnyk, Natalia; Sych, Olga (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2020)
The main purpose of the article is to exam the level of the tax burden on the enterprise, in terms of the impact of this indicator on the financial condition of the entity. For the purpose of this analysis, the data of Ukrainian company were selected, the number of indicators were evaluated, their elasticity and correlation were discussed. Two proposals were developed to decrease the amount of taxes that company payed.
Keywords: taxation; tax burden; tax planning; decreasing of taxation